2018
DOI: 10.3390/rs10121951
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Downward Continuation Values of Airborne Gravity Data in Taiwan

Abstract: An airborne gravity survey was carried out to fill gaps in the gravity data for the mountainous areas of Taiwan. However, the downward continuation error of airborne gravity data is a major issue, especially in regions with complex terrain, such as Taiwan. The root mean square (RMS) of the difference between the downward continuation values and land gravity was approximately 20 mGal. To improve the results of downward continuation we investigated the inverse Poisson’s integral, the semi-parametric method combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This indicated that there was a systematic error (bias) present in the airborne gravity data compared to the terrestrial gravity data. A slightly larger systematic error was found in some other studies, such as: Hwang et al (2007, Table 2), McCubbine (2016, Table 6.5) and Zhao et al (2018), where mean values of the differences were 1.5, 1.0, and − 1.9 mGal, respectively. The expected impact on the determined geoid undulation caused by the bias of airborne gravity data was estimated using Eq.…”
Section: Analysis Of Airborne and Terrestrial Gravity Data Errorsmentioning
confidence: 44%
See 1 more Smart Citation
“…This indicated that there was a systematic error (bias) present in the airborne gravity data compared to the terrestrial gravity data. A slightly larger systematic error was found in some other studies, such as: Hwang et al (2007, Table 2), McCubbine (2016, Table 6.5) and Zhao et al (2018), where mean values of the differences were 1.5, 1.0, and − 1.9 mGal, respectively. The expected impact on the determined geoid undulation caused by the bias of airborne gravity data was estimated using Eq.…”
Section: Analysis Of Airborne and Terrestrial Gravity Data Errorsmentioning
confidence: 44%
“…The method was used in several studies; see, e.g. Alberts and Klees (2004), Barzaghi et al (2009), Goli and Najafi-Alamdari (2011), McCubbine et al (2017), andZhao et al (2018). Global gravity field and topography information were used to remove and restore low-and high-frequency gravity contents before and after DWC.…”
Section: Downward Continuation Of Airborne Gravity Datamentioning
confidence: 99%
“…The accuracy of GraviMob measurements can be then assessed using the downward continued shipborne data. In this study, the Least-Squares Collocation (LSC) approach [20] adapted to the Remove-Compute-Restore (RCR) method was used as it offers several advantages [21][22][23][24][25]. This method enables interpolation anywhere in the 3D space and input data do not need to be at the same height/depth.…”
Section: Downward Continuation Modelmentioning
confidence: 99%
“…Therefore, terrain effects were used to complement EGM2008 in the calculation of the gravimetric geoid/quasi-geoid [35], and the geopotential value for the establishment of a modern local [36,37] or international [38] height reference system. The RTM effects also play an important role in the upward/downward continuation procedure used to validate airborne gravity data (see [23,39,40]). These studies indicated that the incorporation of the RTM effects substantially improved the accuracy of the DC airborne gravity anomalies, especially in mountainous areas.…”
Section: Downward Continuation Of Shipborne Gravity Datamentioning
confidence: 99%
“…The LSC algorithm has been used to estimate crustal movement signals from GPS velocity fields [9][10][11][12][13][14][15]. It has also been used in various earth science fields to control systematic and anomaly errors in GIS spatial data [16], detect outliers in multibeam bathymetric data [17], solve common point coordinate errors in 3D coordinate transformation [18], improve the accuracy of mobile light detection and ranging (LiDAR) systems in hostile environments [19], improve the results of downward continuation values of airborne gravity data [20], and refine the local covariance model of gravity anomalies [21].…”
Section: Introductionmentioning
confidence: 99%